ECONOMIC FEASIBILITY AND PRIORITY DIRECTIONS OF ACTIVIZATION OF SOCIAL INVESTMENTS OF THE ENTERPRISES - O. Grishnova; I. Magdych (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article explores the features of social investment and estimated impact of social investment on key financial and economic indicators of the breweries. Is proved priority areas in social investment and offered to recommendation to improve social investment in the enterprises of the brewing industry in Ukraine.